2018
DOI: 10.1159/000492398
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recombinant Human Growth Hormone in Children with Crohn’s Disease on the Muscle-Bone Unit: A Preliminary Study

Abstract: Background/Aims: There is limited information on the impact of recombinant human growth hormone (rhGH) on the muscle-bone unit in children with Crohn’s disease (CD). In this pilot study, we report on the effects of rhGH on bone formation, dual-energy X-ray absorptiometry (DXA) total body (TB) bone mineral density adjusted for height and lumbar spine (LS) bone mineral apparent density (BMAD), and body composition. Methods: Prospective study of 8 children with CD (6 male), aged 14.8 years (9.0–16.4), who receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the aging process, the levels of GH and IGF-1 show a notable downward trend ( 162 ). Recombinant human GH therapy works by affecting systemic GH and IGF-1 levels, which in turn improves physical function, muscle mass and bone density ( 163 ). However, a number of studies have also reported adverse reactions, including carpal tunnel syndrome, peripheral edema, joint pain and swelling, enhanced female breast development, impaired glucose tolerance and increased cancer risk ( 164 ).…”
Section: Prevention and Treatment Of Osteosarcopeniamentioning
confidence: 99%
“…In the aging process, the levels of GH and IGF-1 show a notable downward trend ( 162 ). Recombinant human GH therapy works by affecting systemic GH and IGF-1 levels, which in turn improves physical function, muscle mass and bone density ( 163 ). However, a number of studies have also reported adverse reactions, including carpal tunnel syndrome, peripheral edema, joint pain and swelling, enhanced female breast development, impaired glucose tolerance and increased cancer risk ( 164 ).…”
Section: Prevention and Treatment Of Osteosarcopeniamentioning
confidence: 99%